Students’ Perception of the Use of Google Classroom in Online Learning During the Covid-19 Pandemic - Abdul Rahman; Zainal Zainal; Asrijal Asrijal; Mardi Mardi; Asriadi Asriadi (Jurnal Literasi Digital, 2021)
This research aimed to determine student perceptions of the use of Google Classroom in online learning during the Covid-19 pandemic. This research applied Descriptive quantitative and a total sample of 147 students. The questionnaire was used in this research to collect the data. The data analysis used was descriptive statistics. The results showed that 61.90% of students responded less agree with the ease of accessing the google classroom application, 72.10% of students who responded strongly agree if they can master the learning material well and easily through the google classroom application, 44.90% of students who responded agreed that this application effective to use in the process of online learning, 47.60% of students responded agreed with the use of the google classroom application for practical courses. The results of students’ perception as a whole were 50.34% of students who responded agreed, 44.22% who responded strongly agreed, 4.76% of students who disagreed, and 0.68% responded that they disagreed and no student responded strongly disagree. It stated that this research received a good and positive response from students’ perception of using Google Classroom application in online learning